Characterization of persistent Listeria monocytogenes strains from ten dry-cured ham processing facilities. (December 2020) - D'Arrigo, Matilde; Mateo-Vivaracho, Laura; Guillamón, Eva; Fernández-León, María Fernanda; Bravo, Daniel; Peirotén, Ángela; Medina, Margarita; García-Lafuente, Ana
Abstract: The majority of cases of listeriosis are associated with the consumption of contaminated food. Some strains of Listeria monocytogenes can persist over months or years in meat processing plants increasing the risk of product contamination. The presence of L. monocytogenes was examined in 10 dry-cured ham processing facilities. A total of 1801 samples were collected from environment and equipment, during processing (1095) and after cleaning and disinfection (706). These samples were taken from non-food contact (736) and food contact (1065) surfaces. In addition, 204 samples from ham surfaces were also analysed. Prevalence varied from 6% to 34% among facilities, and was higher during processing than after cleaning and disinfection (24.8% vs 11.0%) and from non-food than from food contact surfaces (22.6% vs 17.4%). L. monocytogenes serotype 1/2a was predominant (53.9%), followed by 1/2c (26.0%) and 1/2b (15.3%) and less frequently 4b (4.8%). A total of 142 different pulsotypes were registered. Potential persistent L. monocytogenes strains were isolated in 9 out the 10 facilities, with no more than 6 pulsotypes in a given plant. Two pulsotypes were common in different installations, detected before and after cleaning and disinfection, highlighting the importance of monitoring the presence of this pathogen in dry-cured ham processing environments. Highlights: L. monoc ytogenes was found in the environment of ten cured ham processing facilities. Serotype 1/2a was the most prevalent and 1/2b, 1/2c and 4b were also present. A total of 26 persistent PFGE profiles were found. Same PFGE types were detected in different facilities.